2019
DOI: 10.1042/bsr20190112
|View full text |Cite
|
Sign up to set email alerts
|

The resistant effect of SIRT1 in oxidative stress-induced senescence of rat nucleus pulposus cell is regulated by Akt-FoxO1 pathway

Abstract: Objective: The senescence of nucleus pulposus (NP) cells induced by oxidative stress is one of the important causes of intervertebral disc degeneration (IDD). Herein, we investigated the role and action mechanism of silent information regulator 1 (SIRT1) in oxidative stress-induced senescence of rat NP cell. Methods: Premature senescence of rat NP cells was induced by sublethal concentration of hydrogen peroxide (H2O2) (100 μM). SIRT1 was activated with SRT1720 (5 μM) to explore its effect on NP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 53 publications
(66 reference statements)
3
25
0
Order By: Relevance
“…In a complementary approach, we utilized FoxO1 inhibitor AS1842856, which has been used for diabetes and adipogenesis studies (Yu et al, 2018; Zou et al, 2014). AS1842856 has been shown to directly bind and inhibit the active form of FoxO1 (He et al, 2019; Yu et al, 2018). In one study, AS1842856‐mediated inhibition of FoxO showed a dose‐dependent improvement on fasting‐glucose levels in diabetic rodents (Nagashima et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a complementary approach, we utilized FoxO1 inhibitor AS1842856, which has been used for diabetes and adipogenesis studies (Yu et al, 2018; Zou et al, 2014). AS1842856 has been shown to directly bind and inhibit the active form of FoxO1 (He et al, 2019; Yu et al, 2018). In one study, AS1842856‐mediated inhibition of FoxO showed a dose‐dependent improvement on fasting‐glucose levels in diabetic rodents (Nagashima et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…We found that a 10‐fold decrease in AS1842856 permitted chondrogenic differentiation, but did not fully restore SOX9 expression in EtOH‐exposed MSCs. One possible explanation could be that the FoxO1/3 inhibitor may have off‐target effects on other important pathways involved in chondrogenic differentiation such as Sirt1 (He et al, 2019), which has been shown to modulate β‐catenin stability. More likely, FoxO1/3 activity may be required, in at least at some basal level of activity, for osteogenic and chondrogenic differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some studies reported that miR-301a targeted SIRT1, thus attenuating PI3K/AKT and NF-κB signaling pathway ( Chen et al, 2017 ). Junsheng et al reported that SIRT1 inhibits phosphorylation of Akt in the form of negative feedback ( He et al, 2019 ). This confirms the role of SIRT1 in inhibiting inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…SIRT1 is an Nicotinamide adenine dinucleotide (NAD) + -dependent deacetylase that can reduce apoptosis in several different cells. SIRT1 has also been proven to play a protective role in the survival of degenerative human NPCs 26 , 27 , 28 . The underlying mechanism regarding SIRT1 regulation of IDD remains controversial.…”
Section: Discussionmentioning
confidence: 99%
“…A study showed that SIRT1 exerts anti-inflammatory effects against interleukin (IL)-1β-mediated degeneration of NPCs through the Toll-like receptor 2 (TLR2)/SIRT1/nuclear factor κB (NF-κB) pathway, 29 whereas another study showed that SIRT1 ameliorates oxidative stress-induced senescence of rat NPs regulated by the Akt/FoxO1 pathway. 26 miRNAs are highly conserved molecules that can post-transcriptionally regulate protein expression levels. Aberrant miRNA expression has been detected in various musculoskeletal disorders, including osteoporosis, osteoarthritis, rheumatoid arthritis, and IDD.…”
Section: Discussionmentioning
confidence: 99%